Motivation, Attitude and Effort towards Learning English: The Case of Mutah University Jordanian Male and Female Sudents - Alkhrisheh Hazim Taisir Dayij („RIK-U” Kft., 2018)
Abstract. Several studies have been conducted for investigating non-linguistic domains of language learning such as motivation and attitudes towards learning a second or a foreign language in Jordan [1; 4]. The results of these studies show positive attitudes towards learning English, with high levels of instrumental motivation being dominant.
https://kmf.uz.ua/wp-content/uploads/2018/11/Multicult-Diversity_Book-of-Abstracts_23-10-2018.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00006453
Keywords: motivation; attitude; effort; proficiency; gender